Association between a body shape index and bone mineral density in US adults based on NHANES data - Jiabei Wu; Guiping Wu (Scientific Reports)
Abstract The relationship between a body shape index (ABSI) and bone mineral density (BMD) remains uncertain, prompting further investigation. This study aims to elucidate the association between ABSI and BMD using data from the 2011–2018 National Health and Nutrition Examination Survey (NHANES), involving participants aged 20–60. ABSI was calculated using the formula: ABSI = 1000 × waist circumference (m)×weight (kg)−2/3×height (m)5/6. The analysis employed weighted multiple linear regression, smooth curve fitting, stratified analysis, and interaction tests to explore the relationship between ABSI and total BMD. The study included 10,291 participants, with a mean age of 39.11 ± 10.77 years, and 49.20% were women. The average ABSI was 80.21 ± 1.50. Total BMD, thoracic spine BMD, lumbar spine BMD, and pelvis BMD were measured, with mean values of 0.82 ± 0.11 g/cm², 1.03 ± 0.15 g/cm², and 1.24 ± 0.16 g/cm2, respectively. A negative correlation between ABSI and total BMD was observed. In the fully adjusted model, individuals in the highest ABSI quartile had total BMD levels 0.045 g/cm² lower than those in the lowest quartile. Interaction tests showed a consistent association between ABSI and total BMD across subgroups, with variations in sex and BMI. This analysis of NHANES data confirms a persistent negative association between ABSI and BMD, suggesting that ABSI could be useful in osteoporosis prevention and diagnosis.